English Relationship between mothers’ narcissism and the temperament of their children - Celik, Melike Yavas; Guler, Selver (Acta Scientiarum. Health Sciences, 2024)
It was aimed to evaluate the relationship between the narcissism of mothers and the temperament of children which is an important age for personality development. Sample consisted of mothers who wanted to participate in the study and could be reached by using social media (n =470). Young adult mothers with less education living in nuclear families appear to Pathological Narcissism Inventory score higher. The Temperament Scale for Childeren scores of mothers aged 26-35 years were found to be statistically significantly higher than other mothers. The relationship between mothers’ narcissism and their children’s temperament was found to be significant. It has been observed that there is a relationship between narcissism of mothers and temperaments of children.